Authentication, Authorization, Administration and Audit Impact on Digital Security - Navarro, Fauricio Alban Conejo (2024)
We can say technological security is in constant change. Security is constantly changing by the industry, because it is necessary to improve the integrity of technological security. These changes in technology come with new methods, processes, and technologies which lead to the need to be ahead in the new trends. The AAAA (Authentication, Authorization, Administration, Audit) is a topic of great relevance in organizations, it is a matter for everyone. This paper attempts to evaluate the variation presented in the Access Management after implementing digital security plans. The evaluation is visualized as an accompaniment for the improvement of the effectiveness in future decisions-making processes. The result of this analysis aims to find new improvement opportunities, due to the positive impact to growth in this field. The intention is to close the gap between the financial and technological security issues. Nowadays these issues are evaluated individually, and we pretend to unify these subjects.